Kidnapping as a Business Activity and Related Security Implications: A Nigerian Perspective - Brown Egbe Isokon; Ude Bassey Obeten; Oru Takim Tiku; Agnes Ubana Enang; Samson Uche Nwaubani; Okwu Augustina Onyema; Mary Effiong (New Ideas Concerning Arts and Social Studies Vol. 1, 2025)
Kidnapping for ransom has become a serious problem in Nigeria, affecting individuals, families, and society as a whole. While criminals may benefit financially from this illegal activity, the consequences are devastating for victims and hinder the country’s economic growth. The increasing rate of kidnapping has created fear among citizens, discouraged tourism and investment, and posed a major challenge to security management. This study examines the causes of kidnapping and its impact on security and development in Nigeria. The findings suggest that factors like unemployment, poverty, drug abuse, and social inequality contribute to the rise of kidnapping, with many young people getting involved in these crimes. Despite government efforts to tackle the issue, kidnapping continues to spread. To address this problem, society must educate and guide young people toward positive values like honesty, integrity, and non-violence. The government must also take strong action by creating more job opportunities, investing in infrastructure, and reducing poverty to discourage youth from turning to crime. Only by tackling the root causes can Nigeria achieve a safer and more stable society.